Assessment of alkalis released by aggregates. Contribution to the alkalinity increase and AAR development in concrete - Soares, D. (2015)
Concrete swelling processes are one of the main degradation mechanisms of hydro concrete structures, such as dams. Included in this degradation phenomenon, the reactions that involve the aggregates when exposed to the alkali rich environment of the cement paste are probably the ones that deserve more concern worldwide. The alkali concentration of the concrete pore solution could also be modified with time due to the alkalis release from some aggregates or mineral phases present in the aggregate particles, a fact which perhaps could explain the delaying occurrence of AAR in some dams. This paper presents the first results of the evaluation of the alkalis released by different types of aggregates. The results obtained evidence that aggregates containing alkali minerals in their composition are susceptible to alkalis releasing in alkaline solution. This release is thought to be dependent on the mineralogy of the aggregate, the particle size and the type of solution employed. The reactivity of an aggregate, should take into account the alkali content which can release and that may contribute to the AAR.